Arbuscular mycorrhizal fungal association in some commonly occurring economically important plants of Kaziranga National Park, Assam, India - and D.K. JHA*, BIDISHA SHARMA (Indian Phytopathology, 2014)
The present research work involves the study of arbuscular mycorrhizal (AM) fungal diversity in the rhizosphere of some economically important plants existing in grassland and woodland ecosystems of Kaziranga National Park, Assam, India. The rhizosphere soil of twelve economically important plant species belonging to twelve families were sampled of which ten species showed mycorrhizal association while the remaining two species, Lagerstroemium reginae Roxb. and Streblus asper Lour., showed either negligible or complete absence of AM fungal colonization. Forty four AM fungal species belonging to ten genera viz. Acaulospora, Ambispora, Claroideoglomus, Funneliformis, Glomus, Gigaspora, Paraglomus, Rhizophagus, Redeckera and Scutellospora were isolated from the rhizosphere soil of selected plants. Glomus established as the most dominant genus in the study sites, was followed by Acaulospora and Gigaspora. The root colonization and subsequent sporulation of AM fungi were influenced by a wide range of environmental factors. AM spore population varied significantly both due to study sites as well as season. The increased spore population in the rhizosphere in the summer season as compared to either winter or autumn season established summer season as the most favorable season. Results of the present work indicated that Kaziranga National Park have a promising AM fungi diversity which needs to be explored for filing up the gap in the current knowledge of AM fungi diversity in the North-eastern zone of India.